Intravenous chlorpromazine in the acute treatment of episodic tension-type headache: a randomized, placebo controlled, double-blind study - Marcelo Eduardo Bigal; Carlos Alberto Bordini; José Geraldo Speciali (Arquivos de Neuro-Psiquiatria)
Acute headache is a very frequent symptom, responsible for a significant percentage of caseload at primary care units and emergency rooms. Chlorpromazine is easily available in such settings. The aim of this study is to conduct a randomized, placebo-controlled, double-blind study to assess the efficacy of chlorpromazine on the acute treatment of episodic tension-type headache. We randomized 30 patients to receive placebo (10 ml of saline intravenous injections) and 30 patients to receive 0.1 mg/Kg chlorpromazine intravenously. We used 7 parameters of analgesic evaluation. Patients receiving chlorpromazine showed a statistically significant improvement (p < 0.05 and p < 0.01) of pain compared to placebo, far up to 30 minutes after the drug administration. The therapeutic gain was 36.7% in 30 minutes and 56.6 % in 60 minutes. The number needed to treat (NNT, the reciprocal or the therapeutic gain) was 2.7 in 30 minutes and 1.8 in 60 minutes. There were reductions in the recurrence and in the use of rescue medication in the chlorpromazine group. We can conclude that intravenous chlorpromazine is an effective drug to relief the pain in tension-type headache.